Penguatan Karakter Kebangsaan Pada Peserta Didik di SMA Negeri 2 Kota Gorontalo - Adhani, Yuli; Wantu, Sastro M; Rustam, Hardiansyah (Penerbit Widina, Widina Media Utama, 2025)
This collaborative community service between lecturers and students is based on the importance of fostering national character as a means to safeguard students from moral decline. The implementation method consists of two main stages: (1) Preparation, which includes coordination with SMA Negeri 2 Gorontalo as well as the development of materials and supporting tools; and (2) Implementation, which involves interactive counseling through discussions, QA sessions, and simulations held in the hall of SMA Negeri 2 Gorontalo. The results of the study indicate a significant improvement in students’ understanding and behavior related to national values, particularly in the areas of patriotism, tolerance, and social responsibility. The main conclusion of this community service highlights that the collaborative approach and interactive methods are effective in internalizing national values.ABSTRAKPengabdian kolaborasi Dosen dan Mahasiswa ini didasari oleh pentingnya pembentukan karakter kebangsaan sebagai upaya membentengi siswa siswi dari kemerosotan moral. Metode pelaksanaan pengabdian mencakup dua tahap utama: (1) Persiapan, meliputi koordinasi dengan SMA Negeri 2 Gorontalo serta penyusunan materi dan perangkat pendukung; dan (2) Pelaksanaan, berupa penyuluhan interaktif melalui diskusi, tanya jawab, dan simulasi di Aula SMA Negeri 2 Gorontalo. Hasil pengabdian menunjukkan peningkatan cukup pesat dalam pemahaman dan perilaku kebangsaan peserta didik, khususnya dalam aspek cinta tanah air, toleransi, dan tanggung jawab sosial. Kesimpulan dalam pengabdian ini temuan utama menegaskan bahwa pendekatan kolaboratif dan metode interaktif efektif dalam menginternalisasi nilai-nilai kebangsaan.